Augmented reality system for operator support in human–robot collaborative assembly. Issue 1 (2016) - Makris, Sotiris; Karagiannis, Panagiotis; Koukas, Spyridon; Matthaiakis, Aleksandros-Stereos
Abstract: This paper presents the design and implementation of an augmented reality (AR) tool in aid of operators being in a hybrid, human and robot collaborative industrial environment. The system aims to provide production and process related information as well as to enhance the operators' immersion in the safety mechanisms, dictated by the collaborative workspace. The developed system has been integrated with a service based station controller, which is responsible for orchestrating the flow of information to the operator, according to the task execution status. The tool has been applied to a case study from the automotive sector, resulting in an enhanced operator's integration with the assembly process.